Start with distributive properties
32u - 8 - 12u = 22u - 66 Combine like terms
20u - 8 = 22u - 66 Subtract 20u from each side
-8 = 2u - 66 Add 66 to both sides
58 = 2u
u = 29
2006-10-14 16:48:06
·
answer #1
·
answered by PatsyBee 4
·
1⤊
0⤋
(1) Get rid of brackets, then:
8(4u -1)-12u = 11(2u - 6) becomes
32u - 8 - 12u = 22u - 66.
Now transpose all u's to one side & constants on the other:
32u - 12u - 22u = - 66 + 8. Simplifying
(32 - 12 - 22) u = - 58
-2u = - 58 or u = - 58/ - 2 = 29.
Similarly, deal with:
(2) - 5 - (15y - 1) = 2(7y - 16) - y getting
- 5 - 15 y + 1 = 14y - 32 - y. Take all y's on one side and constants on the other:
- 15 y - 14y + y = - 32 + 5 - 1 or
- 28 y = - 28 or y = -28 /-28 or y = 1
2006-10-14 17:05:52
·
answer #2
·
answered by quidwai 4
·
0⤊
0⤋
1/5 (y - 3)= 1/6(y + 4) first you multiply the stuff in the bracket with the stuff outside, so you get: 1/5y - 3/5 = 1/6y +4/6 then you need to find a common factor which is 30 so you times the whole thing by 30 to get rid of the fractions. 30/5y - 90/5 = 30/6y + 120/6 then you simplify ie 30/5 is 6 6y - 18 = 5y + 20 then you collect like terms letters with letters numbers with numbers when you move 5y, which is positive, to the over side it will become a negative, vice visa. so 6y - 5y = y and 20 + 18 = 38 therefore y = 38
2016-05-22 03:04:58
·
answer #3
·
answered by Dorothy 4
·
0⤊
0⤋
The first one you would first distribute the 8 and then the 11. Combine like terms and group then on the sides of the = sign. Same for the 2nd one, distribute the -5 and the 2, combine like terms isolate on sides of = and solve.
2006-10-14 16:48:56
·
answer #4
·
answered by sulfur_and_mercury 1
·
0⤊
0⤋
8(4u-1)-12u=11(2u-6)
32u-8-12u=22u-66
32u-12u-22u=-66+8
-2u=-58
u=29
-5-(15y-1)=2(7y-16)-y
-5-15y+1=14y-32-y
-15y-14y+y=-32-1
-28y=-33
y=33/28=1.179
2006-10-14 16:54:36
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
8(4u-1)-12u=11(2u-6)
32u-8-12u=22u-66
20u-8=22u-66
66-8=22u-20u
58=2u
u=29
-5-(-15y-1)=2(7y-16)-y
-5+15y+1=14y-32-y
15y-4=13y-32
15y+32-4=13y
15y+28=13y
28=13y-15y
28=-2y
y=-14
2006-10-14 19:33:16
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋